Prospects for Precision Medicine in Glomerulonephritis Treatment. Issue 1 (8th February 2018) - Liu, Yulu Cherry; Chun, Justin
Background: Glomerulonephritis (GN) consists of a group of kidney diseases that are categorized based on shared histopathological features. The current classifications for GN make it difficult to distinguish the individual variability in presentation, disease progression, and response to treatment. GN is a significant cause of end-stage renal disease (ESRD), and improved therapies are desperately needed because current immunosuppressive therapies sometimes lack efficacy and can lead to significant toxicities. In recent years, the combination of high-throughput genetic approaches and technological advances has identified important regulators contributing to GN. Objectives: In this review, we summarize recent findings in podocyte biology and advances in experimental approaches that have opened the possibility of precision medicine in GN treatment. We provide an integrative basic science and clinical overview of new developments in GN research and the discovery of potential candidates for targeted therapies in GN. Findings: Advances in podocyte biology have identified many candidates for therapeutic targets and potential biomarkers of glomerular disease. The goal of precision medicine in GN is now being pursued with recent technological improvements in genetics, accessibility of biologic and clinical information with tissue biobanks, high-throughput analysis of large-scale data sets, and new human model systems such as kidney organoids. Conclusion: With advances in data collection, technologies, and experimental model systems, we now have vast tools available to pursue precision medicine in GN. We anticipate a growing number of studies integrating data from high-throughput analysis with the development of diagnostic tools and targeted therapies for GN in the near future.